2022 IEEE International Conference on Big Data (Big Data) 2022
DOI: 10.1109/bigdata55660.2022.10021066
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Trade Flow Prediction by Gravity-informed Graph Auto-encoder

Abstract: The gravity models has been studied to analyze interaction between two objects such as trade amount between a pair of countries, human migration between a pair of countries and traffic flow between two cities. Particularly in the international trade, predicting trade amount is instrumental to industry and government in business decision making and determining economic policies. Whereas the gravity models well captures such interaction between objects, the model simplifies the interaction to extract essential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These models have exhibited their effectiveness across a range of applications, including document labeling, traffic forecasting, and fraud detection [23]. Recently, some research has also used GNN to address the challenges related to international trade in products and services [24][25][26].…”
Section: Graph Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have exhibited their effectiveness across a range of applications, including document labeling, traffic forecasting, and fraud detection [23]. Recently, some research has also used GNN to address the challenges related to international trade in products and services [24][25][26].…”
Section: Graph Neural Networkmentioning
confidence: 99%
“…New methods utilizing causality have been recently introduced to overcome these limitations and enhance the model's generalization capabilities. For example, Minakawa et al [25] proposed a GGAE (Gravity-informed Graph Auto-encoder) and its surrogate model, which draws inspiration from the gravity model. They demonstrated that the surrogate model can solve the edge weight prediction problem in GNNs and that the gravity model's prediction of trade value can be expressed as an edge weight prediction problem [30].…”
Section: Graph Neural Networkmentioning
confidence: 99%